Монгол төрийн легитим, легаль шинж - Ж.Урангуа, (Politology, 2023)
In this article described how" all elevated Mongolia" was proclaimed and it was recognized by the Mongolian society and it was described by the historical sources of that time. An author give her explanation why we should name 1911' events as a revolution and what main purposes were of that revolution and how it was implemented during the revolution.